Aktualisasi Pengabdian Kepada Masyarakat Dalam Melaksakan Pencegahan Covid-19 Di Desa Sambimulyo - Azwar Habibi (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
Covid-19 hit many countries in the world including Indonesia. The Covid-19 outbreak is not only a national problem within a country, but is already a global problem. Covid-19 originated in the Wuhan area of ​​China. The spread of Covid -19, which is so fast and deadly, is transmitted through physical contact through the mouth, eyes and nose. The spread of Covid-19 is out of control, the government invites the public to participate in keeping the spread from spreading by limiting social or physical contact. Community participation is the main key to success in preventing the spread of the Covid-19 outbreak. Social distancing and physical distancing are implemented to cut the chain of spread of the virus.Some people have consciously followed this social restriction mechanism, but some have not participated. This paper examines community participation in preventing the spread of the Covid-19 pandemic in Indonesia. Handling the spread of this virus can be carried out well if the community participates in following the government's advice to always maintain a safe distance from one another, one of which is to stay at home. Covid-19 is an epidemic virus and has the potential for a public health emergency. In the Bangorejo sub-district itself, the government and various local community institutions in dealing with this epidemic have implemented several programs and policies to minimize and prevent the Covid-19 outbreak, but in reality some people do not heed the appeals and directions from the government or social institutions.